Case report: Utilization and efficacy of large-bore catheters in mechanical thrombectomies - Bhattacharyya, Meghna; Badger, Clint A.; Jankowitz, Brian T.; Shaikh, Hamza A. (Frontiers in Neurology, 2023)
Thrombotic strokes are caused by occlusion of flow in a blood vessel by a clot or thrombus, resulting in disruption of oxygen and nutrients to the brain that can result in neurological deficits. There are many devices now available for safe and effective removal of thrombi from large blood vessels. This report focuses on the Zoom 0.088” large-bore catheter, which has the potential to be navigated into a large vessel for thrombus removal via aspiration, and weigh the risks and benefits of its utilization in thrombectomy patients. In this case, we discuss the use of this device for thrombectomy of a left M1 middle cerebral artery occlusion that resulted in a distal left MCA dissection and eventual loss of access to the site of the thrombus. Ultimately, the patient died from a large stroke in the left MCA territory. In light of this occurrence, we seek to explore the utility and feasibility of large-bore catheters and their risks in thrombectomy candidates.